2009
DOI: 10.1038/leu.2008.354
|View full text |Cite
|
Sign up to set email alerts
|

Effective in vivo induction of NKG2D ligands in acute myeloid leukaemias by all-trans-retinoic acid or sodium valproate

Abstract: Engagement of NKG2D by their ligands (NKG2D-L), as the human major histocompatibility complex class I-related molecules MIC-A and the UL16-binding proteins, on cytolytic lymphocytes leads to the enhancement of antitumour effector functions. These ligands are missing or expressed at very low levels on leukaemic cells; furthermore, they can be shed by tumour cells and inhibit cytolytic activity of lymphocytes. Herein, we show that in vivo administration of all-trans-retinoic acid (ATRA) or the histone deacetylas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
100
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(106 citation statements)
references
References 25 publications
6
100
0
Order By: Relevance
“…In this study, we showed that VPA elevated the expression of MICA and B on the surface of osteosarcoma cells and enhanced their susceptibility to the cytotoxicity of NK cells as reported with other tumor cells (6)(7)(8)(9)(10)(11). On the other hand, levels of soluble MICA and B were not changed or rather decreased in the presence of VPA.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In this study, we showed that VPA elevated the expression of MICA and B on the surface of osteosarcoma cells and enhanced their susceptibility to the cytotoxicity of NK cells as reported with other tumor cells (6)(7)(8)(9)(10)(11). On the other hand, levels of soluble MICA and B were not changed or rather decreased in the presence of VPA.…”
Section: Discussionmentioning
confidence: 54%
“…HDAC inhibitors which alter the histone acetylation status have been shown to induce cell cycle arrest and apoptosis in various tumor cells (4,5). In addition, HDAC inhibitors stimulate the expression of cellsurface MICA and B on tumor cells to enhance cytotoxicity of NK cells and host immune surveillance against tumor cells (6)(7)(8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…83,99 All-transretinoic acid and the histone deacetylase inhibitor sodium valproate were repeatedly shown to induce NKG2D ligand expression in certain types of tumors, including AML, 44,100,101 leading to an improved sensitivity to NK cell-mediated killing. Promotors of myeloid cell differentiation trichostatin A and vitamin D3 were also shown to upregulate NKG2D ligands on AML cells.…”
Section: Nk Cell Immune Escape In Aml E Lion Et Almentioning
confidence: 99%
“…A number of studies have demonstrated that HDAC inhibitors stimulate the expression of cell surface MICA and MICB in a variety of tumors (12)(13)(14)(15). Valproic acid (VPA), a HDAC inhibitor, increases the expression of MICA and MICB on the surface of human osteosarcoma cells (16).…”
Section: Introductionmentioning
confidence: 99%